2012
DOI: 10.4103/0976-3147.102638
|View full text |Cite
|
Sign up to set email alerts
|

Miliary brain metastases from occult lung adenocarcinoma: Radiologic and histopathologic confirmation

Abstract: “Miliary brain metastases”, also termed as “Carcinomatous encephalitis”, are an extremely rare form of cerebral metastasis. Here in this article, we report a 52 year-old male patient with miliary brain metastases originating from occult lung adenocarcinoma. There were no significant findings on his initial physical and neurological examinations except limited cooperation. Brain computed tomography revealed edematous regions at the inferior sections of both parietal lobes. Then after, the contrast-enhanced magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Apart from meningeal carcinomatosis, the brain metastases also showed an unusual spread confined to the Virchow–Robin spaces, referred to as carcinomatous encephalitis. This spread is seldom associated with intra-parenchymal invasion, undetected in plain skull films and computed tomography, but better demonstrated by magnetic resonance imaging,[ 8 ] as noted in our case as well. The condition poses a clinical challenge as symptoms are diverse.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Apart from meningeal carcinomatosis, the brain metastases also showed an unusual spread confined to the Virchow–Robin spaces, referred to as carcinomatous encephalitis. This spread is seldom associated with intra-parenchymal invasion, undetected in plain skull films and computed tomography, but better demonstrated by magnetic resonance imaging,[ 8 ] as noted in our case as well. The condition poses a clinical challenge as symptoms are diverse.…”
Section: Discussionsupporting
confidence: 71%
“…Some patients are asymptomatic, whereas others have symptoms that mimic psychiatric, metabolic, or infective disorders. [ 8 ] Our patient had a clinical diagnosis of conversion reaction. On literature review, about 24 cases have been reported, with the majority of the metastases originating from papillary/micropapillary pulmonary adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,11,12 We have occasionally encountered advanced lung cancer patients with multiple miliary metastatic lesions on distant organs. [13][14][15] We collectively refer to miliary intrapulmonary and distant site metastases as "milary dissemination carcinomatosis" and describe its clinical phenotype in lung adenocarcinomas with EGFR mutations in this study. We also compare the response of miliary and non-miliary disseminated carcinomatosis to EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%